Representation and Application of Jacket Knowledge Based on Domain Ontology (Journal of Fiber Bioengineering and Informatics, 2021)
This paper takes jacket as an example, constructs a clothing knowledge model based on domain ontology, and explores ways to represent and reuse clothing knowledge in the context of the Internet economy. In this paper, jacket knowledge is sorted out based on the dimension of life week of clothing products, and the jacket knowledge framework is subdivided under the guidance of the modular design concept, laying a foundation for further application of the framework. The research shows that combining ontology modeling technology and knowledge representation, jacket domain ontology can be constructed to realize the classification of jacket design knowledge. This paper also further discusses the application prospect of jacket knowledge framework, which can play a guiding role in the customization of the jacket and modular design of the jacket, improve the reuse rate of jacket knowledge, and provide a feasible application mode for garment knowledge management.
Keywords: Jacket; Product Life Cycle; Knowledge Classification; Knowledge Framework